Penerapan Enterprise Risk Management dalam Kegiatan Bongkar Muat Kontainer pada PT Dunia Express Transindo (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to identify, assess, and control risks that arise in container loading and unloading activities at PT Dunia Express Transindo using the Enterprise Risk Management (ERM) approach. Container loading and unloading activities are complex and involve various parties, making them highly susceptible to risks, both from internal and external aspects. Risks that can occur include system disruptions, operational negligence, equipment damage, and environmental factors such as extreme weather that can affect the smoothness of the loading and unloading process. Therefore, the company needs to have a structured, comprehensive, and sustainable risk management system to maintain operational continuity. This research method refers to the COSO framework and the ISO 31000:2018 standard which focuses on the process of risk identification, assessment of likelihood and impact levels, and formulation of appropriate mitigation strategies. Data were obtained through interviews with management, field observations, and analysis of company documents. The results of the study indicate that the implementation of ERM is able to map risks more systematically, making it easier for the company to determine handling priorities. Several risks with a high probability and significant impact received special attention through the implementation of mitigation strategies such as improving information technology systems, routine employee training, and more scheduled equipment maintenance. These findings indicate that ERM implementation not only functions as a risk control tool but also plays a role in increasing operational efficiency, strengthening inter-departmental coordination, and minimizing potential losses that could disrupt company stability. Furthermore, ERM implementation makes a real contribution to increasing the competitiveness of companies in the logistics and stevedoring sector, especially in facing dynamic business challenges and external environmental uncertainty.